(untitled) (International Seven Journal of Multidisciplinary, 2025)
Introduction: Urological surgery plays a critical role in the management of conditions related to occupational diseases. This study analyzes the impacts of surgical intervention on workers exposed to occupational risks, such as chemical substances, intense physical efforts and inadequate postures. Objectives: This review article aims to analyze and synthesize the evidence available in the literature on the impacts of urological surgery on occupational diseases. Methodology: This article adopts a systematic literature review approach to identify, select and analyze relevant studies on the impacts of urological surgery on occupational diseases. Results and Discussion: The results indicate that surgery can significantly contribute to improving the quality of life and functionality of patients, although it also highlights challenges, such as prolonged recovery and impact on labor reintegration. Conclusion: Greater attention is recommended to primary prevention and multidisciplinary rehabilitation to minimize occupational consequences and facilitate return to work.